Identity, trust and altruism: An experiment on preferences and microfinance lending - Josie I. Chen; Andrew D. Foster; Louis G. Putterman (Brown University, Department of Economics, 2017)
We construct a dedicated web interface and use it to conduct a laboratory experiment to study willingness to lend and preference over borrowers in micro-finance lending. We distinguish between perceptions of transaction-related factors, such as neediness and trustworthiness, and identity-related factors such as ethnicity and gender. By looking at both channels together we are able to assess the extent to which identity-related differences in lending can be attributed to differences in how transaction-related factors are perceived among people with similar and different identities. We find that (1) both financial return and philanthropic motivation affect the amount lent, with little evidence that the former crowds out the latter; (2) lenders have a statistically significant preference for borrowers with whom they share gender and ethnic similarity even after controlling for perceived riskiness, neediness, and other factors including physical attractiveness and weight; and (3) lenders are willing to trade greater risk in order to help more needy borrowers, but at a rate sensitive to their own degree of financial exposure.
Keywords: C91; D64; O17; J15; 330; microfinance; pro-social preferences; gender; ethnicity; homophily; discrimination